Foetal and female genital growth in the Surti buffalo - BAISHYA, G; VYAS, K N (The Indian Journal of Animal Sciences, 2013)
Female genitalia from clinically healthy Surti buffalo foetuses (39) were studied at 6 different phases of intra-uterine life, ranging from 67 to 305 days (8.5 to 102.5 cm CVR). An increase in curved crown-rump length (CVR) of the foetuses was noticed with the advancement of age. The foetal body weight and combined weight of all the genitalia revealed different values in different age groups. However, themaximum foetal growth and development were observed from 240 to 305 days (74.0 to 102.5 cm CVR) in the age group 6. The growth pattern of developing female genitalia as a whola in relation to foetal growth rale followed no consistent trend. It is concluded that in general the relative growth rate decreased with advancing gestational age in Surti buffalo.